Development of Pop-Up Book Based Mathematics Learning Media on Three-Dimensional Shapes Material for Elementary School Students - Andreansyah, Refi; Sari, Eka Yuliana (research, training and philanthropy institution Natural Aceh, 2024)
Most students consider mathematics a complex subject. Many students complete assignments and tests and receive low scores. This is often due to the monotonous nature of mathematics Learning, which makes students bored and uninterested. This study aims to develop a Learning media based on pop-up books that are both valid and feasible, with an attractive design that can be used in the Learning process and address student challenges. This research employs a Research and Development (R&D) approach using the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). Data collection techniques include media, material, and language validation questionnaires and student response questionnaires. The results indicate that the pop-up book Learning Media is highly valid and features a perfect design, as evidenced by the validation results: media at 88%, material at 86%, and language at 91.5%, all within the valid/feasible category. Product trials were conducted in two stages: a small group trial at SDN 4 Ngentrong (with five students) yielded an 89% rating, and a large group trial at SDN I Wajak Lor (with 23 students) yielded an 88.2% rating both within the outstanding category. Thus, the development of the pop-up book-based Learning media is highly valid and suitable for use as a Learning tool for three-dimensional shapes in fifth-grade elementary school, and it features an attractive and perfect design.